2020
DOI: 10.1038/s41598-020-76077-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intense storm events on dolphin occurrence and foraging behavior

Abstract: As storms become increasingly intense and frequent due to climate change, we must better understand how they alter environmental conditions and impact species. However, storms are ephemeral and provide logistical challenges that prevent visual surveys commonly used to understand marine mammal ecology. Thus, relatively little is known about top predators’ responses to such environmental disturbances. In this study, we utilized passive acoustic monitoring to characterize the response of bottlenose dolphins to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In a line transect distance sampling framework, the probability of detecting an object is a function of many factors other than distance of the object from the track-line, including group-size, species and habitats, as well as sea state (e.g., Holt and Cologne, 1987;Thomas et al, 2012;Fandel et al, 2020). Numerous studies have demonstrated that detection varies among species, over time, and among habitats, and there may be serious consequences when this variability is ignored.…”
Section: Design-based Abundance Estimatesmentioning
confidence: 99%
“…In a line transect distance sampling framework, the probability of detecting an object is a function of many factors other than distance of the object from the track-line, including group-size, species and habitats, as well as sea state (e.g., Holt and Cologne, 1987;Thomas et al, 2012;Fandel et al, 2020). Numerous studies have demonstrated that detection varies among species, over time, and among habitats, and there may be serious consequences when this variability is ignored.…”
Section: Design-based Abundance Estimatesmentioning
confidence: 99%
“…PAM is already used for a multitude of biological applications. Examples include monitoring, characterizing and delineating underwater soundscapes, and investigating aquatic communities (e.g., Desjonquères et al, 2015;Erbe et al, 2015;Menze et al, 2017;Mooney et al, 2020;Stanley et al, 2021); documenting the distribution and migration patterns of the great whales (e.g., Risch et al, 2014;Tsujii et al, 2016;Davis et al, 2020;Warren et al, 2021); characterizing the spatial and temporal responses of fish choruses to environmental drivers like temperature, salinity, lunar phase, tide, and time of sunset (e.g., Barrios, 2004;Rountree et al, 2006;Parsons, 2010;Straight et al, 2015;Rice et al, 2016;McWilliam et al, 2017;Parsons et al, 2016;Karaconstantis et al, 2020;Linke et al, 2020); understanding how animals change their behavior and distribution in response to climate change (Gordon et al, 2018), anthropogenic noise sources (e.g., Thompson et al, 2013;Cerchio et al, 2014;Erbe et al, 2019;Meekan et al, 2021), algal blooms (e.g., Rycyk et al, 2020) and extreme weather events like hurricanes (e.g., Locascio and Mann, 2005;Fandel et al, 2020;Boyd et al, 2021;Schall et al, 2021); understanding how prey change their sound production rates or behaviors with the presence of predators (e.g., Luczkovich and Keusenkothen, 2007;Hughes et al, 2014;Bailey et al, 2019;Burnham and Duffus, 2019); and how noise and propagation conditions can affect communication spaces (e.g.,…”
Section: Introductionmentioning
confidence: 99%
“…However, globally, a number of studies have documented epidermal and biochemical changes associated with prolonged low salinity exposure (in both free swimming and stranded dolphins), including skin lesions, electrolyte imbalance, microbial infection and death [32][33][34][35][36][37][38], in addition to a disrupted prey environment affecting foraging [39]. In addition, data exist on behavioral and physiological responses in dolphins when water salinity is varied in a controlled manner or through natural events (i.e., hurricanes, floods, entrapments) [26,32,40] but die-offs have been associated with such instances [24,33,34].…”
Section: Introductionmentioning
confidence: 99%